2021
DOI: 10.1002/bit.27877
|View full text |Cite
|
Sign up to set email alerts
|

An engineered cellobiohydrolase I for sustainable degradation of lignocellulosic biomass

Abstract: This study provides computational‐assisted engineering of the cellobiohydrolase I (CBH‐I) from Penicillium verruculosum with simultaneous enhanced thermostability and tolerance in ionic liquids, deep eutectic solvent, and concentrated seawater without affecting its wild‐type activity. Engineered triple variant CBH‐I R1 (A65R‐G415R‐S181F) showed 2.48‐fold higher thermostability in terms of relative activity at 65°C after 1 h of incubation when compared with CBH‐I wild type. CBH‐I R1 exhibited 1.87‐fold, 1.36‐fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
(156 reference statements)
0
10
0
Order By: Relevance
“…The 12 filtered beneficial substitutions were divided into two categories based on the CompassR rule: Subset 1: ΔΔ G fold ≤+0.36 kcal mol −1 , which could be predictably beneficially recombined (S12C, S12K, S12V, S12A, T77M, E85Y, G264H, G264R, D290G); Subset 2: 0.36<ΔΔ G fold ≤+7.52 kcal mol −1 , which showed unpredictable recombinants (S3T, S3P, F80Y). This general cutoff had been successfully applied to engineer the catalytic properties of several enzymes [10b, 11a, 15, 33] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 filtered beneficial substitutions were divided into two categories based on the CompassR rule: Subset 1: ΔΔ G fold ≤+0.36 kcal mol −1 , which could be predictably beneficially recombined (S12C, S12K, S12V, S12A, T77M, E85Y, G264H, G264R, D290G); Subset 2: 0.36<ΔΔ G fold ≤+7.52 kcal mol −1 , which showed unpredictable recombinants (S3T, S3P, F80Y). This general cutoff had been successfully applied to engineer the catalytic properties of several enzymes [10b, 11a, 15, 33] …”
Section: Resultsmentioning
confidence: 99%
“…Recently, several knowledge-acquiring strategies, such as KnowVolution, [11] Com-passR (Computer-assisted Recombination), [12] and 2GeReP, [13] were used to maximize the performance of evolved enzymes and minimize the experimental effort by balancing directed evolution and computational analysis. [14] Studies on numerous enzymes (e.g., Bacillus subtilis lipase A (BSLA), [10b] cellobiohydrolase I, [15] TEM-1 β-lactamase, [16] avGFP [17] and transketolase [18] ) showed that the relative folding free energy (ΔΔG fold ) is an essential factor in predicting the evolvability of proteins. Previously, the In Silico guided Recombination Process (InSiReP) adopted a computationally directed strategy applying ΔΔG fold to recombine the beneficial substitutions/recombinants based on the obtained experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…These findings could assist in the planning of rational approaches to the design of new enzyme friendly ILs and to the engineering of new IL-tolerant enzymes. The success achieved to date in improving the tolerance of cellulases to ILs in some of the rational approaches is promising (Lee et al 2017 ; Pramanik et al 2021 ; Summers et al 2020 ). Important aspects to consider in planning are that enzymes differ in their response to various ILs and that different substrates may behave differently in IL solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The glucose analysis of hydrolysis samples was determined using a Somogyi-Nelson method (Pramanik et al, 2021). Measurement of glucose concentration was conducted by spectrophotometer.…”
Section: Glucose Determinationmentioning
confidence: 99%